2016
DOI: 10.1039/c5ra24854j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced purification of carbon nanotubes by microwave and chlorine cleaning procedures

Abstract: A new two-step purification method of carbon nanotubes (CNTs) involving a microwave treatment followed by a gas-phase chlorination process is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 40 publications
1
36
0
3
Order By: Relevance
“…As noted in the introduction, we have been concerned with issues associated with the presence of residual catalyst particles in SWCNTs with regard to any meaningful investigation of their reactivity. Based upon prior work, we suggested that the presence of oxidized Cr species is due to a reaction with the iron oxide catalyst residue that is commonly present [21,22,27].…”
Section: Reaction Of Cr(co) 6 With Iron Oxidementioning
confidence: 99%
See 2 more Smart Citations
“…As noted in the introduction, we have been concerned with issues associated with the presence of residual catalyst particles in SWCNTs with regard to any meaningful investigation of their reactivity. Based upon prior work, we suggested that the presence of oxidized Cr species is due to a reaction with the iron oxide catalyst residue that is commonly present [21,22,27].…”
Section: Reaction Of Cr(co) 6 With Iron Oxidementioning
confidence: 99%
“…However, these treatments add oxygen functional groups [16,32], which are possibly detrimental to the chemistry of interest. We have previously reported that microwaving SWCNTs in air causes carbon-encapsulated iron to break out of its carbon shell and be oxidized, facilitating its chemical removal with acid or chlorine [27]. In an adaptation of the prior procedure, raw HiPco SWCNTs were subjected to microwave irradiation followed by refluxing in concentrated hydrochloric acid to dissolve the iron oxides, and finally annealing to 550 • C to remove oxygen functional groups, adsorbed oxygen, and any remaining acid residue.…”
Section: Xps Analysis Of Swcnt Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…All tubing used for the reactor was Teflon™ obtained from Cole-Palmer or United States Plastic Corp (Shanghai, China). Chlorine treatment of SWCNTs was adapted from the literature [25].…”
Section: Materials and Characterizationmentioning
confidence: 99%
“…Кроме того, углеродная оболочка защищает железосодержащие наночастицы от окисления, предотвращает спонтанную агломерацию и изменение их свойств [5][6][7]. С другой стороны, во многих случаях наличие частиц метал-лического катализатора в УНТ является нежелатель-ным [8,9]. Имеется большое число работ, направленных на удаление металлических частиц с использованием методов мокрой химии (например, кислотной обработки в H 2 SO 4 /HCl) или термической обработки в инертных средах [10][11][12].…”
Section: Introductionunclassified